2020
DOI: 10.1007/s00432-020-03302-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and comparison of the outcome in young versus older patients with upper gastrointestinal carcinoma

Abstract: Background The clinical behaviour and outcome of young patients with gastroesophageal tumours (GET) is surmised to differ from older patients, yet data on the comparison of these two patient subgroups is scarce. This study focuses on the investigation of the clinical characteristics and survival outcome of younger-age people with GET, when compared to older patients. Methods Patients diagnosed with GET at the Medical University of Vienna between 2004 and 2016 were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…In our study, the 5 year survival of young patients was very poor (14.1%), the 1-year and 3-year survival rates for the 99 cases were 67.7% and 24.2%, respectively. Young GC patients showed poor prognosis, which was consistent with the results of Puhr et al [46] Their study showed that the 5 year survival of patients under 45 years was 17%. Our study found that TNM stage was significantly associated with the prognosis of young GC ( P < .05), which was also consistent with previous studies, [9] suggesting a pivotal importance of early diagnosis.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, the 5 year survival of young patients was very poor (14.1%), the 1-year and 3-year survival rates for the 99 cases were 67.7% and 24.2%, respectively. Young GC patients showed poor prognosis, which was consistent with the results of Puhr et al [46] Their study showed that the 5 year survival of patients under 45 years was 17%. Our study found that TNM stage was significantly associated with the prognosis of young GC ( P < .05), which was also consistent with previous studies, [9] suggesting a pivotal importance of early diagnosis.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, at the multivariate analysis, age (≤40 years), gender (female), clinical stage (IV), and primary tumor location (gastric) remained predictors of worst prognosis and OS. These variables have also been correlated among other studies including different population such as Chinese ( 9 , 35 ), Korean ( 3 ), American ( 29 , 34 ), and European ( 37 , 38 ), concluding that young female patients are commonly diagnosed at a metastatic stage of the disease and have worst outcome and higher risk of death.…”
Section: Discussionmentioning
confidence: 73%
“…This information shows that young female patients are predominantly diagnosed at metastatic disease stage (59%), with tumor location at stomach (70%), histological classification of diffuse type (68%), signet ring cell component (72%); and poor differentiation (90%). All clinical features related to a bad prognosis of OS and outcome in other studies worldwide ( 14 , 24 , 35 ). Thus, we performed a sub-analysis regarding clinical stage of the disease.…”
Section: Discussionmentioning
confidence: 76%
“…L. Cheng et al продемонстрировали, что показатели общей 5-летней выживаемости среди двух возрастных подгрупп 18-49 и 50-59 лет составили 62,4 и 70,8 % (p=0,019), с неудовлетворительными данными в отношении 5-летней безрецидивной выживаемости -75,2 и 82,8 % (p=0,040), сопряженными с высокими рисками метахронного перитонеального интраабдоминального рецидива, диагностируемыми в 3 раза чаще у более молодых пациентов (15,1 и 5,2 %, p<0,01) [31]. H.C. Puhr et al сообщают, что при сопоставимых критериях отбора, включающих пол, морфологию опухоли, локализацию и распространенность патологического процесса, медиана ОВ с локализованной и местнораспространенной формами больных РЖ в младшей (до 45 лет) и старшей (от 65 лет и старше) возрастных группах составила 41,8 и 26,7 мес (p=0,028), а при наличии синхронных интра-либо экстраабдоминальных метастазов -15 и 21,5 мес (p=0,033) [32]. В одном из китайских исследований при сравнении пациентов с РЖ до 45 и старше 50 лет за период 3-летнего наблюдения в группах радикально оперированных больных не выявлено существенной разницы при оценке общей выживаемости, составляющей 70,4 и 75,9 % (p=0,3881) при сопоставимых показателях регионарного рецидива либо отдаленного метастазирования -40,7 и 43,5 % (p=0,514) [33] [36].…”
Section: Introductionunclassified